Regional Economic Growth in Colombia: the role of Fiscal corruption and the Armed conﬂict - Herrera Gomez, Marcos Hernan (2024)
This research explores the impact of armed violence and corruption on the economic growth of Colombia’s departments from 1991 to 2017. Using models of spatial panels, statics and dynamics, we detect positive space-time indirect eﬀects on departmental growth, including evidence of beta-convergence. Speciﬁcally, ﬁscal corruption exhibited a signiﬁcant negative impact on short-term economic growth. Moreover, corruption primarily aﬀected growth at the local level, with limited spillover eﬀects observed from neighboring regions. Interestingly, our analysis did not yield statistically signiﬁcant evidence regarding the impact of armed violence on economic growth.